Office Setting as Organizational Structure in “Bartleby the Scrivener” - Lori Duin Kelly (SAGE Open, 2017)
This article uses a methodology from the social sciences known as institutional ethnography to analyze the office setting in Herman Melville’s short story “Bartleby the Scrivener” as a site of social organization. This approach contributes to an understanding of how that office came to adopt specific structures as crucial to its functioning and how, as a consequence of those structures, individuals’ roles within the organization’s hierarchies became constituted. As fieldwork occurs inside of organizations, institutional ethnography also provides a tool for identifying and evaluating linguistic markers for an individual’s placement within a larger organizational structure. This approach to the story seems particularly useful for understanding the interpersonal dynamics at the heart of “Bartleby.” At the same time, it provides a method for identifying the larger institutional process at work in Melville’s story, one that contributes to the reproduction of a system of social relations in the workplace that requires subordination and compliance to insure its success.